FREE WEIGHT TRAINING VS. ELASTIC BAND TRAINING: WHAT IS A MORE EFFECTIVE STRATEGY FOR INCREASING MAXIMAL VELOCITY ABILITY DURING HANDBALL THROWS? (Kinesiology, 2023)
The aim of this study was to assess the effectiveness of two resistance training (RT) programmes (free weight [FW] and elastic band [EB]) on velocity variables (handball throwing velocity [HTV] and maximal theoretical velocity [V0]) using load-velocity (L-V) relationship modelling. Both programmes lasted 6 weeks and consisted of performing bench press and overarm dumbbell pull-over using free weights (FW group) or elastic bands (EB group). Nineteen male sports science students were randomly assigned to EB (n=10) or FW group (n=9). Both RT programmes increased HTV and V0, although the increment was greater in the FW (>2 m·s-1) compared to the EB group (